KOMPETENSI GRAMATIKAL DAN KONTEKSTUAL MAHASISWA JURUSAN BAHASA INGGRIS DALAM MENULIS PARAGRAF EKSPOSITORI - Dwi Areni, Galuh Kirana (Lingua, 2011)
This study focuses on the competence of grammatical and discourse of English Department students, especially their competence in using correct tense and word order, and in using good coherence-cohesion and unity-completeness. This research aims at gaining a description whether the students have applied both competence well in writing their expository paragraphs. There are two research questions addressed in the study 1) How is the studentsÃ¢â¬â¢ grammatical competence, which is realized in the use of correct grammar and word order,ÃÂ  in their expository paragraphs?; 2) How is the studentsÃ¢â¬â¢ discourse competence, which is realized in the use of good coherence-cohesion and good unity-completeness, in their expository paragraph? The object of the study is the expository paragraphs of Paragraph-based Writing class, English Educational study program, semester 3 in 2009-2010 academic year. There are 32 paragraphs as population, 6 of them were taken randomly as research sample. The procedure of collecting the data was carried out by distributing the intrument of the study in the form of outside-class assignment. Later, the students had to submit their assignments in printed forms. The data were analyzed by using the Azar theory (1989) for the use of tense and word order, and the Boardman-Frydenberg theory (2002) for the use of coherence-cohesion and unity-completeness. Based on the data analysis, it was found out that for the grammatical competence, the most frequent error in studentsÃ¢â¬â¢ expository paragraphs is the use of tense. Whereas, for the discourse competence, the most frequent error in studentsÃ¢â¬â¢ expository paragraphs is the error in using cohesive devices such as the use of transition signals, pronoun, article, dan demonstrative pronoun. Finally, the pedagogical implication of the study is the students are supposed to fully motivated to be active outside their Writing classes in order to improve their grammatical and discourse competence in writing paragraphs. ÃÂ  Keywords: grammatical competence, discourse competence, tense, word order, coherence, cohesion, unity, completeness